From hearing with a cochlear implant and a contralateral hearing aid (CI/HA) to hearing with two cochlear implants (CI/CI): a within-subject design comparison - Luntz, Michal; Egra-Dagan, Dana; Attias, Joseph; Yehudai, Noam; Most, Tova; Shpak, Talma (Otology & neurotology, 2014)
To compare within-subject bilateral-binaural and bimodal complementary abilities between bimodal (cochlear implant and hearing aid; CI/HA) and bilateral CI hearing (CI/CI), thereby enabling better-informed counseling of experienced CI/HA users contemplating contralateral implantation. Comparative within-subject case review. Outpatient hearing clinic. Ten experienced adult CI/HA users with severe-to-profound hearing loss in the HA ear, who converted to CI/CI between 2 and 11 years after initial implantation. Task-specific testing of bilateral-binaural hearing (sound lateralization, binaural summation/redundancy/unmasking, head-shadow effect), bimodal complementary benefit (contribution of low-frequency information), and a self-report Speech, Spatial, and Qualities of Hearing (SSQ) questionnaire, all before and 1 year after contralateral cochlear implantation. Test result differences between CI/HA and CI/CI conditions. CI/CI hearing was better than CI/HA for speech lateralization and for perception of semantically unpredictable sentences in speech noise with speech at 0 degrees and noise at +90 degrees azimuth on the old CI side. CI/HA was better than CI/CI only for differences between perception of natural prosody speech and of speech with flattened fundamental frequency (F0) contour with speech and noise in front (at 0 degrees azimuth). Total scores on the SSQ questionnaire were higher in CI/CI than in CI/HA users. Counseling regarding contralateral implantation for CI/HA users with severe-to-profound hearing loss in the HA ear, though generally positive, should consider individual functional needs, and cover expectations about the expected trade-off between gaining improved understanding and speech lateralization in challenging listening conditions and losing some low-frequency cues still available with CI/HA hearing.